Investigating Users' Natural Spatial Mapping between Drone Dimensions and One-Hand Drone Controllers - Büttner, Sebastian; Heinz, Mario; Zanini, Paulo; Röcker, Carsten (Proceedings of the International workshop on Human-Drone Interaction (iHDI'19) as part of the ACM Conference on Human Factors in Computing Systems (CHI '19))
Using remote control transmitters is a common way to control a drone. For the future, we envision drones that are intuitively controllable with new input devices. One possibility could be the use of one-hand controllers, e.g. 3-D mice. While developing such a device, we investigated the users’ natural spatial mapping between controller and drone dimensions. In this paper we present our insights about this mapping and show why relative position control is an important control concept for novice users.